Nonverbal working memory for novel images in rhesus monkeys - Brady, Ryan J. (Curr Biol, 2018)
Human working memory is greatly facilitated by linguistic representations, for example by verbal rehearsal and by verbal re-coding of novel stimuli. The absence of language in nonhumans raises questions about the extent to which nonhuman working memory includes similar mechanisms. There is strong evidence for rehearsal-like active maintenance in working memory when monkeys are tested with highly familiar stimuli, but not when tested with novel stimuli, suggesting that working memory depends on the existence of previously encoded representations. This difference in working memory for familiar and novel images may exist because, lacking language, monkeys cannot re-code novel stimuli in a way that permits active maintenance in working memory. Alternatively, working memory for novel images may have been present, but behaviorally silent, in earlier studies. In tests with novel images, the high familiarity of to-be-remembered stimuli compared to never before seen distractors may be such a strong determinant of recognition performance that evidence of working memory is obscured. In the current study, we developed a technique for attenuating the utility of relative familiarity as a mnemonic signal in recognition tests with novel stimuli. In tests with novel images, we observed impairments of memory by concurrent cognitive load, and by delay interval, that indicate actively maintained working memory. This flexibility in monkey working memory suggests that monkeys may re-code unfamiliar stimuli to facilitate working memory, and establishes new parallels between verbal human working memory and nonverbal nonhuman primate working memory.